Building for war the epic saga of the civilian contractors and marines of Wake Island in World War II - Gilbert, Bonita L. (Casemate, 2012)
This is the story of the thousand-plus Depression-era civilian contractors who came to Wake Island, a remote Pacific atoll, in 1941 to build an air station for the U.S. Navy. The civilian contractors who had risked distance and danger for well-paying jobs ended up paying a steep price: their freedom and, for many, their lives.